STARTING YOUR SHORT STORY: Questions to help you identify your story - Sonya Gildea (UCD Writing Centre, 2023)
Most writers agree that the best way to discover your story is through the process of writing it. However, at the outset, you may be unsure of what your story is or how to start writing it. This can be daunting. Ask yourself the key creative and technical questions below so as to help you identify your story and to develop your initial ideas, images, characters or scenes into a complete work of fiction.